Digital Music Library: Selcuk University - Kılıçaslan, Fatma (Information World, 2004)
The aim of this article is to give explanatory information concerning the Digital Music Library which is situated at the Selcuk University Central Library. The information provided includes development and future goals of the mentioned library together with gained experience throughout the time. Some condensed user information has been supplied too.
Keywords: Electronic music library; Music library; Digital library; Electronic resources; Digitization